(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
This article provides information on the pedagogical and psychological laws of legal and educational work, as well as the psychological analysis of offenses committed by young people, the stages of its formation, and the general analysis of existing psychological approaches to these cases.